2022
DOI: 10.3892/mmr.2022.12762
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00961 regulates endothelial‑mesenchymal transition via the PTEN‑PI3K‑AKT pathway

Abstract: The long noncoding RNA LINC00961 plays a crucial role in cancer and cardiovascular diseases. In the present study, the role and underlying mechanism of LINC00961 in endothelial-mesenchymal transition (EndMT) induced by transforming growth factor beta (TGF-β), was investigated. Human cardiac microvascular endothelial cells were transfected with LV-LINC00961 or short hairpin LINC00961 plasmids to overexpress or knock down LINC00961 in the cells, respectively. The cells were then exposed to TGF-β in serum-free me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For example, EndMT plays an important role in pathophysiological processes such as myocardial ischemia-reperfusion, MI, diabetic cardiomyopathy, and fibrosis. There is an example: EndMT plays an important role in pathophysiological processes such as myocardial ischemia-reperfusion, myocardial infarction, diabetic cardiomyopathy, and fibrosis; and TGF-β-induced EndMT can be attenuated by knocking down the LINC00961 by a mechanism related to activation of phosphatase and tensin homolog (PTEN) expression and inhibition of PI3K, AKT, and mammalian target of rapamycin (mTOR) ( Hu et al, 2022 ). mTOR, as a PI3K- Akt downstream gene, mainly regulates the cardiac fibrosis by affecting the expressions of pro-fibrotic factors.…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 99%
“…For example, EndMT plays an important role in pathophysiological processes such as myocardial ischemia-reperfusion, MI, diabetic cardiomyopathy, and fibrosis. There is an example: EndMT plays an important role in pathophysiological processes such as myocardial ischemia-reperfusion, myocardial infarction, diabetic cardiomyopathy, and fibrosis; and TGF-β-induced EndMT can be attenuated by knocking down the LINC00961 by a mechanism related to activation of phosphatase and tensin homolog (PTEN) expression and inhibition of PI3K, AKT, and mammalian target of rapamycin (mTOR) ( Hu et al, 2022 ). mTOR, as a PI3K- Akt downstream gene, mainly regulates the cardiac fibrosis by affecting the expressions of pro-fibrotic factors.…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 99%
“…Phosphatase and tensin homolog (PTEN) plays an important role in regulating embryonic development and cell growth, differentiation, apoptosis, and migration, and it mainly exerts biological functions by controlling cell signal transduction pathways. PTEN has phosphatase activity and can regulate downstream pathways through phosphorylation and dephosphorylation 7,8 . PI3K/Akt signaling pathway receives inhibitory regulation by PTEN, an important signaling pathway that regulates cell growth, proliferation, survival, and apoptosis, and it regulates glycogen synthesis and glucose conversion, which are closely associated with reduced cell proliferation and apoptosis 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…PTEN has phosphatase activity and can regulate downstream pathways through phosphorylation and dephosphorylation. 7,8 PI3K/Akt signaling pathway receives inhibitory regulation by PTEN, an important signaling pathway that regulates cell growth, proliferation, survival, and apoptosis, and it regulates glycogen synthesis and glucose conversion, which are closely associated with reduced cell proliferation and apoptosis. 9,10 Zhuang et al 11 established a rat knee fibrosis model by knee immobilization, and found that the decreased PTEN gene expression in fibroblasts in fibrotic joints, followed by decreased PTEN protein translation expression, activated PI3K/AKT signaling pathway, which promoted myofibroblast proliferation and facilitated the development of joint fibrosis.…”
Section: Introductionmentioning
confidence: 99%